Effect of Various Preterm Infant Milk Formulas on NEC-Like Gut Injury in Mice - Rao, Karishma; Cuna, Alain; Chavez-Bueno, Susana; Menden, Heather; Yu, Wei; Ahmed, Ishfaq; Srinivasan, Pugazhendhi; Umar, Shahid; Sampath, Venkatesh (Frontiers in Pediatrics, 2022)
Formula feeding is an important risk factor for the development of necrotizing enterocolitis in preterm infants. The potential harmful effects of different preterm formulas on the developing intestinal tract remain incompletely understood. Here we demonstrate that feeding newborn mouse pups with various preterm formulas resulted in differing effects on intestinal inflammation, apoptosis, and activation of the pro-inflammatory transcription factor NFκB. 16S rRNA sequencing revealed that each preterm formula resulted in significant gut microbial alterations that were different from dam-fed controls. Formula feeding with EleCare and Similac Special Care caused greater intestinal injury compared to NeoSure. Pre-treatment with Lactobacillus rhamnosus GG ameliorated severity of intestinal injury from EleCare and Similac Special Care. Our findings indicate that not all preterm formulas are the same, and different formulations can have varying effects on intestinal inflammation, apoptosis, and microbiome composition.